The Relationship Between the Long-Term Non-Rehabilitated Benign Paroxysmal Positional Vertigo and Vestibular Hypofunction - Dastan Temirbekov; Erdal Sakallı; Gamze Kılıç (Haseki Tıp Bülteni, 2021)

(untitled)
Aim:Recurrent Benign paroxysmal positional vertigo (BPPV) and vestibular hypofunction (VH) can be co-diagnosed in some patients. We aimed to sight the relationship between the recurrent BPPV and VH, and to evaluate the change in the VH prevelance according to recurrent BPPV duration.Methods:We conducted a retrospective chart review of 416 patients who were diagnosed with recurrent BPPV. Demographic features of the patients, co-diagnosis frequency of recurrent BPPV and VH, and the change in the VH prevelance according to recurrent BPPV duration were recorded. Patients were divided into two groups for having BPPV attacks for more than 12 months or less than 12 months. Both groups were compared in terms of VH prevalence.Results:VH was co-diagnosed in 61.7% of patients with BPPV. The age of the recurrent BPPV patients with VH was significantly higher than the patients without VH (p<0.05). VH positivity was directly correlated with the duration of recurrent BPPV. VH prevelance was significantly higher in the group that the BPPV duration was above 12 months than in the group that the recurrent BPPV duration was under 12 months (p<0.05).Conclusion:VH is common in patients with recurrent BPPV. There is may be a causal relationship between BPPV and VH.